Personal tools

Talk:The Monad.Reader/Issue3/Notes on Learning Haskell

From HaskellWiki

Jump to: navigation, search

I fail to see, in the first example, why

t :: (Char->Float) -> (Float->Int) -> Char -> Int
t f g c = g . f c

is a 'valid form'. The code is the same as the code above it. Just some variables have been renamed.

It also results in the same error message. Shouldn't this be:

t :: (Char->Float) -> (Float->Int) -> Char -> Int
t f g c = (g . f) c

Or am I missing something obvious?